Optimizing and Guiding English Language Skills for Male Students at Islamic Boarding School - Razaq, Yusuf; Adzim, Syahrun; Inayah, Nur; Fahira, Ainun; Nurhidayanti (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2022)
Students can study in non-formal schools as well as formal schools, such as by participating in training to improve their grasp of a lesson. However, being able to attend the course is unquestionably costly. Some of the kids hailed from low-income homes, found it difficult to balance their studies with their busy lives at Islamic boarding schools, lacked enthusiasm for studying English and lacked English language manuals other than school textbooks, among other symptoms. Therefore, the goal of this service activity is to help students at the As'adiyah Sengkang Islamic boarding school improve and guide their English skills. This service activity is conducted using a fun training style that includes games, singing, and short chats. The result of this service is that students' English skills have improved as a result of this optimization and guidance, as evidenced by an increase in students' average English scores from 78 on the initial test to 87 on the final test. It can be concluded that using the training and direct guidance method to improve students' English at the men's boarding school, As'adiyah Sengkang is an effective way to improve students' English.